The impact of cultural and language barriers on the academic performance of Arab postgraduate students - Khairi Obaid, Al-Zubaidi, Assoc. Prof. Dr.; Richards, Cameron, Prof. (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.